355 SULFONAMIDE HYPERSENSITIVITY AND SUCCESSFUL DESENSITIZATION IN A PATIENT WITH END-STAGE RENAL DISEASE. (1st January 2005) - Vital, C. J.; Mabudian, M.; Kamboj, S.; Kumar, P.
Abstract : Background: Trimethoprim-sulfamethoxazole (TMP-SMX) is widely considered the initial drug of choice for the treatment and prophylaxis of Pneumocystis jiroveci (PCP) in HIV infected patients as well as non-HIV infected patients peritransplantation and post solid organ transplantation. However, there are no published data regarding safe and effective TMP-SMX desensitization regimens in non-HIV, immunocompetent patients with renal failure. We present a safe and successful TMP-SMX desensitization protocol peritransplantation for a patient with renal failure and a history of generalized pruritis and maculopapular rash after consumption of TMP-SMX. Methods: A 41-year-old woman with end-stage renal disease secondary to lupus and TMP-SMX hypersensitivity was desensitized via a 2-day protocol based on the patient's creatinine clearance. The starting dose given was 0.001 mg of TMP-SMX orally, increasing the dose ever 30 minutes until the therapeutic dose of 400 mg orally once daily was achieved. Results: Tryptase levels were drawn before desensitization and after completion of the protocol and these levels remained within normal limits. The patient tolerated the procedure well, experiencing only one episode of pruritis that lasted 5 minutes on day one of desensitization, which resolved without intervention. She was able to continue her TMP-SMX at therapeutic doses before and after her renal transplant without incident. Conclusion: This case report demonstrates successful desensitization with TMP-SMX in a non-HIV, immunocompetent patient with end-stage renal disease. This helped to enable the patient to have optimal PCP prophylaxis, minimize morbidity and mortality, and undergo a successful kidney transplant.